Primary gingival tuberculosis in pregnancy: A rare combination - Shweta Sharma; Abdul Ahad; Narinder Dev Gupta; Vivek Kumar Sharma (Wolters Kluwer Medknow Publications, 2018)
Tuberculosis (TB), a common chronic-specific granulomatous disease, has become rare in the developed countries. However, it is still a common cause of morbidity and mortality in India. Although it commonly involves the lungs, its presentation in the oral cavity is quite uncommon. The very rare incidence of primary gingival TB, particularly in the absence of active pulmonary involvement often leads to misdiagnosis. Clinical features of oral lesions may include ulceration, nodules, granulomas, and fissures. TB in pregnant women is a major cause of obstetric complications and increased risk of maternal and child mortality. This report highlights a rare case of primary TB of gingiva, presenting as severe gingival overgrowth in a patient with 4th month of pregnancy. This case strongly suggests the importance of suspecting TB as the differential diagnosis of gingival overgrowth and therefore, playing a critical role in the early detection and treatment. Interdisciplinary collaboration for diagnosis and management resulted in the successful outcome and prevented the obstetric complications in this case.